2018
DOI: 10.1186/s13054-018-2276-6
|View full text |Cite
|
Sign up to set email alerts
|

Mild decrease in heart rate during early phase of targeted temperature management following tachycardia on admission is associated with unfavorable neurological outcomes after severe traumatic brain injury: a post hoc analysis of a multicenter randomized controlled trial

Abstract: BackgroundThe association between isolated admission heart rate (HR) and prognosis has been discussed, but not that between gross HR change and neurological outcome in patients with severe traumatic brain injury (TBI). In the acute phase of severe TBI, HR is influenced by several factors (e.g., pain, sympathetic activation, hypovolemia, fever, body temperature). Therefore, admission HR and gross HR change should be examined in patients with TBI treated with a well-designed protocol, such as was done in the Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Tachycardia (HR > 100 bpm), in patient with trauma, could be an indicator of hypovolemic shock that may negatively impact the CPP. This negative effect worsens when tachycardia is associated with low SBP (< 90 mmHg) which leads to poor TBI outcomes [ 38 , 41 ]. The mean HR upon admission to the emergency room following TBI was 102.8 beats per min while the mean HR upon arrival for those who died was 107.7 beats per minute.…”
Section: Discussionmentioning
confidence: 99%
“…Tachycardia (HR > 100 bpm), in patient with trauma, could be an indicator of hypovolemic shock that may negatively impact the CPP. This negative effect worsens when tachycardia is associated with low SBP (< 90 mmHg) which leads to poor TBI outcomes [ 38 , 41 ]. The mean HR upon admission to the emergency room following TBI was 102.8 beats per min while the mean HR upon arrival for those who died was 107.7 beats per minute.…”
Section: Discussionmentioning
confidence: 99%
“…Further, presenting heart rate (HR) is an indicator of the patient's hemodynamic stability following any type of trauma particularly TBI. High HR (> 100 bpm) [42] especially when associated with Low SBP (< 90 mmHg) [40] may indicate hypovolemic shock state which leads to poor CPP. This study found a positive relationship between the HR and in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the adjusted predicted probabilities of 30-day favorable neurological outcome and 30-day survival, we used multiple logistic regression model adjusted for age > 65 [21, 22], gender [21, 23], witness [24], dispatcher instruction [25, 26], bystander CPR [24, 27], cardiac etiology [28], initial shockable rhythm [29, 30], prehospital epinephrine administration [31], prehospital advanced airway management [32], time from call to hospital arrival [33, 34], prehospital ROSC [35, 36], Glasgow Outcome Scale score [37], coronary angiography [38], extracorporeal membrane oxygenation (ECMO) and/or intra-aortic balloon pumping (IABP) [22, 39], and PaCO 2 30–50 mm Hg [40, 41], as performed in previous studies [23, 42].…”
Section: Methodsmentioning
confidence: 99%